The Creative Process Of Finding Ideas Of Undergraduate Students Of Malang State University In Writing Poetry - Muhammad Irfan; Wahyudi Siswanto; Nita Widiati (Eduvest - Journal of Universal Studies, 2024)
When literary works are important to study, the creative process of creating works also deserves to be studied in more depth. This study discusses the creative process of undergraduate students from the Department of Indonesian Language, Literature and Regional Education in writing poetry. The purpose of the study is to find out how the creative process is in writing poetry. This study produced findings in the form of a creative process in searching for ideas in the form of activities. It is hoped that the benefits of this study can contribute to how students look for ideas for poetry essays.